Función de los consultorios jurídicos en el posconflicto (2021)
This article is an advance of a research on the situation of the victims of the armed conflict in the post-conflict after the signing of the Peace Agreement between the Colombian State and the Revolutionary Armed Forces of Colombia (Fuerzas Armadas Revolucionarias de Colombia - Ejército del Pueblo) (FARC-EP) which  proposes  the signing of an agreement between the Ombudsman's Office and the Special Jurisdiction for Peace (JEP) as mechanisms to streamline the response capacity of this corporation. This agreement would allow law students assigned to legal clinics of Colombian law schools to join the  Autonomous System of Free Counseling and Defense (SAAD), as a mechanism to achieve an adequate service for low-income victims of the armed conflict, understanding that the consolidation of what is proposed in the treaty signed by the parties requires that low-income victims of the armed conflict have a preferential treatment that ensures them a comprehensive care, if the construction of a new model of society is to be achieved. To this end, it is assumed that the service of legal clinics to low-income victims of the armed conflict would improve the implementation of the SAAD regulated in Decree 1166 of July 11, 2018.